2008
DOI: 10.1016/j.neulet.2008.08.076
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor 2 is increased in acutely and chronically inflamed bladder of rats

Abstract: Cannabinoid receptors 1 and 2 (CB1 and CB2) are G-protein coupled receptors that are expressed throughout the body. Cannabinoid receptor are expressed in the urinary bladder and may affect bladder function. The purpose of this study was twofold: to confirm the presence of cannabinoid receptors in the bladder, the L6/ S1 spinal cord, and dorsal root ganglia (DRG), and to determine the effects of acute and chronic bladder inflammation on expression of cannabinoid receptors. Acute or chronic bladder inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 23 publications
6
57
0
Order By: Relevance
“…It will be interesting for future studies to clarify this by using co-localisation of nerve fibres with CB1 receptors to identify the type of nerve fibres altered in the suburothelium and detrusor of patients with DO. A role for CB2 receptors in bladder dysfunction has been suggested by the finding of upregulation of receptor expression in rat bladders with acute and chronic inflammation [24] and in MS patients with neurogenic DO [23]. Similarly, we found increased CB2 receptor expression in the mucosa of patients with DO and a decrease in receptor expression in the detrusor of these patients, suggesting altered CB2 function in the urinary bladder that is related to disease.…”
Section: Discussionsupporting
confidence: 75%
“…It will be interesting for future studies to clarify this by using co-localisation of nerve fibres with CB1 receptors to identify the type of nerve fibres altered in the suburothelium and detrusor of patients with DO. A role for CB2 receptors in bladder dysfunction has been suggested by the finding of upregulation of receptor expression in rat bladders with acute and chronic inflammation [24] and in MS patients with neurogenic DO [23]. Similarly, we found increased CB2 receptor expression in the mucosa of patients with DO and a decrease in receptor expression in the detrusor of these patients, suggesting altered CB2 function in the urinary bladder that is related to disease.…”
Section: Discussionsupporting
confidence: 75%
“…Since then, it has been shown that a number of different CB 2 R agonists can modulate many types of pain, i.e. acute, inflammatory, neuropathic, post-surgical and cancer pain [33,34,35,36,37,38,39,40,41,42,43,44]. It is still not completely clear where these CB 2 R agonists exert their analgesic activity.…”
Section: Cannabinoids For the Treatment Of Pain: Preclinical And Animmentioning
confidence: 99%
“…In several experiments, spinal cannabinoid CB 2 Rs were not up-regulated by different inflammatory processes such as CFA-induced paw inflammation [42] and CFA-induced arthritis [43] or acrolein-induced bladder inflammation in rats [44]. …”
Section: Cannabinoids For the Treatment Of Pain: Preclinical And Animmentioning
confidence: 99%
“…Similarly, the presence of the endocannabinoid system in the urinary bladder has led to speculation that endocannabinoid-signalling is involved in the signal transduction pathways regulating bladder relaxation and may be involved in pathophysiological processes of the bladder. This role of the endocannabinoids in the lower urinary tract supports their therapeutic potential in conditions of OAB and DO, whereas evidence already exists for their role in bladder inflammation [2,59,75,84]. There are still a number of unanswered questions in the understanding of cannabinoid pharmacology in the urinary bladder.…”
Section: The Futurementioning
confidence: 87%
“…CB 1 receptors are mainly found at the central and peripheral neuron terminals of the bladder, inhibiting neurotransmitter release [55]. Several studies have localized both cannabinoid receptors in the urinary bladder of humans rats mice and monkeys [2,[55][56][57][58][59][60]. The localization of CB 1 receptors has been described to be in the urothelium and nerve fibres of the suburothelium and in human and rat detrusor muscle [2,58,60].…”
Section: Cannabis and The Urinary Bladder Cannabinoid Receptor Distrimentioning
confidence: 99%